Marked decrease in coil and stent utilization following introduction of flow diversion technology. (27th April 2012) - Crobeddu, Emanuela; Lanzino, Giuseppe; Kallmes, David F; Cloft, Harry J
Abstract : Background: Flow diversion represents a major paradigm shift in the treatment of unruptured intracranial aneurysms. The potential impact of this technique on coil utilization and adjunctive techniques such as balloon-assisted and stent-assisted coiling is unknown. In this study, the effect of introduction of flow diversion devices on the utilization of coil and adjunctive techniques was assessed. Methods: A retrospective review was conducted of consecutive patients with unruptured aneurysms treated at our institution comparing two groups: Group 1 (patients treated in the 2-year interval preceding the introduction of the Pipeline Embolization Device (PED) and Group 2 (patients treated during the 2-year interval following introduction in our practice of the PED). Results: Mean aneurysm diameter was 8.7±6.3 mm in Group 1 and 8.5±6.1 mm in Group 2 (p=0.79). PED therapy was employed in 38 (21.7%) of 175 aneurysms in Group 2. The proportion of stent-assisted procedures was significantly less in Group 2 than in Group 1 (6.9% vs 14.7%, p=0.04), as was the proportion of patients undergoing parent artery sacrifice (0.6% vs 3.9%, p=0.046). The mean and median number of coils used per aneurysm were 5.4±3.6 and 5 (range 1–18) for Group 1 and 3.2±3.2 and 3 (range 0–19) for Group 2 (p≤0.0001). Conclusions: Flow diversion represents a disruptive technology. More than one-fifth of unruptured aneurysms at our institution were treated with PED after introduction of this technology, resulting in marked decreases in coil and stent utilization.